Body mass index and efficacy and safety of ticagrelor versus prasugrel in patients with acute coronary syndromes - Lahu, Shqipdona; Behnes, Michael; Ndrepepa, Gjin; Neumann, Franz-Josef; Sibbing, Dirk; Bernlochner, Isabell; Menichelli, Maurizio; Mayer, Katharina; Richardt, Gert; Gewalt, Senta; Angiolillo, Dominick J.; Coughlan, John Joseph; et al. (Revista española de cardiología. English version, 2022)
Introduction and objectives - The efficacy and safety of ticagrelor vs prasugrel in patients with acute coronary syndromes (ACS) according to body mass index (BMI) remain unstudied. We assessed the efficacy and safety of ticagrelor vs prasugrel in patients with ACS according to BMI. - Methods - Patients (n=3987) were grouped into 3 categories: normal weight (BMI <25kg/m2; n=1084), overweight (BMI ≥ 25 to <30kg/m2; n=1890), and obesity (BMI ≥ 30kg/m2; n=1013). The primary efficacy endpoint was the 1 year incidence of all-cause death, myocardial infarction, or stroke. The secondary safety endpoint was the 1 year incidence of Bleeding Academic Research Consortium type 3 to 5 bleeding. - Results - The primary endpoint occurred in 63 patients assigned to ticagrelor and 39 patients assigned to prasugrel in the normal weight group (11.7% vs 7.5%; HR, 1.62; 95%CI, 1.09-2.42; P=.018), 78 patients assigned to ticagrelor and 58 patients assigned to prasugrel in the overweight group (8.3% vs 6.2%; HR, 1.36; 95%CI, 0.97-1.91; P=.076), and 43 patients assigned to ticagrelor and 37 patients assigned to prasugrel in the obesity group (8.6% vs 7.3%; HR, 1.18; 95%CI, 0.76-1.84; P=.451). The 1-year incidence of bleeding events did not differ between ticagrelor and prasugrel in patients with normal weight (6.5% vs 6.6%; P=.990), overweight (5.6% vs 5.0%; P=.566) or obesity (4.4% vs 2.8%; P=.219). There was no significant treatment arm-by-BMI interaction regarding the primary endpoint (Pint=.578) or secondary endpoint (Pint=.596). - Conclusions - In patients with ACS, BMI did not significantly impact the treatment effect of ticagrelor vs prasugrel in terms of efficacy or safety. Clinical Trial Registration: NCT01944800. - Resumen - Introducción y objetivos - Siguen sin estudio la eficacia y la seguridad del ticagrelor frente al prasugrel en pacientes con síndrome coronario agudo (SCA) según el índice de masa corporal (IMC). Se evaluaron la eficacia y la seguridad del ticagrelor frente a prasugrel en pacientes con SCA según el IMC. - Métodos - Se agrupó a los pacientes (n=3.987) en 3 categorías: con peso normal (IMC <25; n=1.084), sobrepeso (IMC ≥ 25-<30; n=1.890) y obesidad (IMC ≥ 30; n=1.013). El objetivo primario de eficacia fue la incidencia de muerte por cualquier causa, infarto de miocardio o accidente cerebrovascular a 1 año. El objetivo secundario de seguridad fue la incidencia de hemorragias de tipo 3-5 de la Bleeding Academic Research Consortium a 1 año. - Resultados - El objetivo primario se produjo en 63 pacientes asignados a ticagrelor y 39 asignados a prasugrel en el grupo de peso normal (el 11,7 frente al 7,5%; HR=1,62; IC95%, 1,09-2,42; p=0,018), 78 pacientes asignados a ticagrelor y 58 asignados a prasugrel en el grupo de sobrepeso (el 8,3 frente al 6,2%; HR=1,36; IC95%, 0,97-1,91; p=0,076) y 43 pacientes asignados a ticagrelor y 37 asignados a prasugrel en el grupo de obesidad (el 8,6 frente al 7,3%; HR=1,18; IC95%, 0,76-1,84; p=0,451). La incidencia de eventos hemorrágicos a 1 año en los pacientes con peso normal (el 6,5 frente al 6,6%; p=0,990), sobrepeso (el 5,6 frente al 5,0%; p=0,566) u obesidad (el 4,4 frente al 2,8%; p=0,219) no difirió entre el ticagrelor y el prasugrel. No hubo una interacción significativa entre el brazo de tratamiento y el IMC en relación con el objetivo primario (pinteracción=0,578) o el secundario (pinteracción=0,596). - Conclusiones - En pacientes con SCA, el IMC no influyó significativamente en el efecto del tratamiento con ticagrelor en términos de eficacia o seguridad frente al prasugrel.
Online verfügbar: 24. Dezember 2021, Artikelversion: 21. August 2022
Gesehen am 26.09.2023